A daydream and a nightmare in Muqaddar Ka Sikandar: Formulas, fantasies and 1970s action Hindi cinema. Issue 1 (1st December 2022) - Trivedi, Pragya
1970s Hindi formula films have been described within Hindi film scholarship as melodramatic, and masochistic fantasies, the latter in terms of the hero's desire to return to a pre-Oedipal state. In my analysis of Muqaddar Ka Sikandar (1978), the biggest hit of the year, I focus on its staging of scenes of fantasy and dream-like episodes and its foregrounding of childhood episodes involving father substitutes, primary figures I argue in the staging. By examining the film's psychical–spatial terrain, I also consider the figure of the rival and villain, played by Amjad Khan, and I argue that Khan's villainy reworks scenes of staged enmity with the hero into reconciliation. I conclude with some observations on the contemporary circulation of formula films on YouTube, where the films and their songs remain remarkably popular and generate a large archive of likes, views and comments, and user-generated content.